Assessment of potential impacts in tourism of the increase in the average sea level - Gomes, Pedro (2018)
Climate change and its effects are inevitable according to many authors; policies should be assumed regarding their mitigation and adaptation. Some economic sectors may suffer negative impacts, being tourism one with greater potential for impact. The increase in average sea level is one of the potential effects of climate change that can have consequences on tourism, particularly in the travel destinations that include coastal regions. The main objective of this work is to propose an approach for the assessment of potential impacts of the increase in the average sea level of tourism in a coastal area with a tripartite methodology. This methodology includes the assessment of physical vulnerability of the coast, including a coastal vulnerability index composed by nine physical variables – elevation, distance to shore, tide amplitude, significant wave weight, erosion/accretion rates, geology, geomorphology, ground cover vegetation and anthropogenic actions – followed by a quantification of coastal recession, based on the Bruun rule and the data of Special Report on Emissions Scenarios (SRES) developed by the Intergovernmental Panel on Climate Change (IPCC), on the rise in average sea level. Finally, it is estimated the total economic value of an area of recreation and tourism, based on the travel cost method. The proposed methodology was applied to a case study in the Portuguese coast, corresponding to the beach of São Jacinto, in Aveiro.